Upper secondary students' perception towards kinesthetic learning activities conducted in an english classroom: an insight - Sain, Noridah (2007)
This research focuses on upper secondary students’ perceptions of kinesthetic learning activities conducted in secondary level English classroom. It also investigates the types of kinesthetic learning activities that are beneficial to upper secondary students and the challenges that the students encounter while taking part in kinesthetic learning activities. This research which is mainly qualitative and descriptive in nature employs the use of several research strategies utilizing written Style Analysis Survey, written journal responses, direct observation and interviews. The sample of six subjects comprised of form four students of Mara Junior Science College Batu Pahat, Johor. These subjects were identified through purposive sampling after they have taken the Style Analysis Survey. This study reveals several important findings, one of which is that kinesthetic learning activities benefited learners in a number of ways: movement to prevent boredom, movement to eliminate stress and movement to encourage social interaction. Subjects mainly agreed that they do rely on teacher guidance to be catalyst for the kinesthetic learning activities and realized that there were negative factors about kinesthetic activities. The research also discovered that subjects equated kinesthetic learning activities with learning which would encourage fun learning experiences.